Faktor-Faktor yang Mempengaruhi Peluang Pencari Kerja Dalam Mangakses Internet di Sumatera Barat - Hilda Wiranti; Alpon Satrianto (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This study aims to determine (1) the effect of the level of education on the opportunities for job seekers to access the internet in West Sumatra. (2) the influence of gender on job seekers' opportunities to access the internet in West Sumatra. (3) the influence of age on the opportunities for job seekers to access the internet in West Sumatra. (4) the influence of the area of residence on the opportunities for job seekers to access the internet in West Sumatra. (5) the effect of income on job search opportunities in accessing the internet in West Sumatra. This type of research is descriptive - associative. The types and sources of data from the Socio-Economic Survey are secondary. In this study using data that already exists in a data collection (National Socio-Economic Survey (SUSENAS) in 2018. The analysis tool used is logistic regression analysis, and the total number of job seekers is 1,641 people. From the results of this study, it is explained that (1) education has a significant positive effect on the opportunities for job seekers to access the internet in West Sumatra, (2) gender has no significant negative effect on the opportunities for job seekers to access the internet in West Sumatra. (3) age has no significant positive effect on the opportunities for job seekers to access the internet in West Sumatra (4) the area of residence has a positive and significant effect on the opportunities for job seekers to access the internet in West Sumatra. (5) income has a significant positive effect on the opportunities for job seekers to access the internet in West Sumatra. As for the results of the research, so that the government of West Sumatra Province can provide socialization on the use of the internet in looking for work and become a consideration for the government in formulating a policy related to job availability for job seekers in accessing the internet.